Unveiling Practical Insights: An Assessment of Media Influence on Tertiary Students' Perceptions of Crime and Criminals in Jigawa State (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study examines the influence of media on tertiary students' perceptions of crime and criminals in Jigawa State, Nigeria. With the rise in media consumption, particularly of crime-related content, there is growing concern about its potential to distort reality and elevate fear of crime among young adults. Utilizing Gerbner’s Cultivation Theory as a framework, this research explores how different media types impact students' understanding of crime, including television, social media, and news outlets. A mixed-method approach was used, combining surveys and focus group discussions with students across various institutions. The results indicate a significant correlation between high media consumption and exaggerated crime perception. Findings further reveal that students frequently exposed to sensational crime stories report heightened fear and misconceptions about criminal activity. These insights underscore the need for media literacy programs and balanced crime reporting to mitigate the influence of media on students' perceptions of crime.